Application of molecular assay for adenovirus detection among different pediatric patients - Puerari,Diane (2015)
OBJECTIVE: Adenoviruses play an important role in the etiology of severe acute lower respiratory infection, especially in young children. The aim of the present study was to evaluate the Human Adenovirus (HAdV) detection by different methods (Direct Fluorescence Assay DFA and Nested Polymerase Chain Reaction nested PCR), among samples collected from different groups of pediatric patients. METHODS: Collection of samples was made in children with congenital heart disease (CHD 123 nasal aspirates collected in the years of 2005, 2007 and 2008) and in community children (CC 165 nasal aspirates collected in 2008). Children were eligible if they presented acute respiratory infection (ARI) of probable viral etiology, within up to 7 days of symptoms' onset. All studied samples were evaluated by DFA and nested PCR assay. RESULTS: Of the 290 samples included during the study period, 43 (14.8%) were positive on at least one test: 17/165 (10.3%) of the CC and 26/125 (20.8%) of the CHD children. The nested PCR detection rates in the community children were 15/165 (9.1%), and for children with CHD, 24/125 (19.2%). Molecular method showed higher detection rates when compared to the DFA test (p<0.001). Univariate analysis showed that children with congenital heart disease presented a significantly higher chance for acquiring the HAdV (Odds Ratio 2.3; 95% CI: 1.18-4.43). CONCLUSIONS: Based on data obtained in the present evaluation, we suggest that a routine surveillance should be performed in high risk patients by molecular methods, thus improving diagnostic flow and efficiency.